Analysis of Nursing Care for Post Appendixitis Patients with Acute Pain Nursing Problems Through Providing Distraction Using a Stress Ball in the Kemoning Room Klungkung Regional General Hospital - Widiningsih, Ni Putu Putri; Sari, Ni Luh Putu Dian Yunita; Prihandani, I GAA Sherlyna (PROMOTOR, 2025)
Patients with appendicitis are a very common problem in the community. Complications that often arise due to appendicitis include perforation, so it is necessary to treat quickly for appendicectomy. Appendicectomy can cause complications such as acute pain, to overcome pain problems in patients, pain management is needed, namely distraction using stress balls. This Ners Final Scientific Work was carried out to determine the analysis of nursing care in post appendicitis patients with acute pain nursing problems through the provision of distraction using stress balls. The results of the assessment obtained the main complaints of the three patients were pain in the surgical wound in the lower right abdomen, a scale of 5-7, a nursing plan to provide distraction using a stress ball, nursing action by providing distraction using a stress ball carried out for 2 x meetings. The results of nursing evaluations carried out on the three managed cases showed that all of them experienced a decrease in pain from a moderate pain scale to a mild pain scale. It is recommended to Klungkung Regional General Hospital to establish distraction using stress ball as a standard operating procedure in pain management.